Effect of Good Corporate Governance, KAP Reputation, Its Size and Leverage on Integrity of Financial Statements - Nurdiniah, Dade; Pradika, Endra (International Journal of Economics and Financial Issues, 2017)
This study aims to determine the effect of good corporate governance, the reputation of the firm, company size and leverage to the integrity of financial statements. The dependent variable in this study is the integrity of the financial statements is measured with conservative accounting model of Beaver and Ryan. Independent variables used are independent directors, audit committee, institutional ownership, and the reputation of the firm, company size and leverage. Data analysis method used is multiple linear regression analysis. The research proves that independent commissioners and the size of the company's reputation KAP positive effect on the integrity of the financial statements of companies listed on the Indonesian Stock Exchange (BEI) in the period 2013-2015 while the audit committee, institutional ownership and leverage do not affect the integrity of the financial statements of companies listed on the Indonesian Stock Exchange (BEI) in the period 2013-2015. Keywords: Integrity Financial Statements, Good Corporate Governance, Reputation KAP, Company Size, Leverage. JEL Classification: G3